Biological Properties and Clinical Significance of Lipoprotein-Associated Phospholipase A2 in Ischemic Stroke. (14th October 2022) - Zhang, Shuang; Huang, Shuchun; Hu, Dingju; Jiang, Fenglong; Lv, Yanli; Liu, Guoqi
Abstract : Ischemic stroke, which occurs following blockage of the blood supply to the brain, is a leading cause of death worldwide. Its main cause is atherosclerosis, a disease of the arteries characterized by the deposition of plaques of fatty material on the inner artery walls. Multiple proteins involved in the inflammation response have been identified as diagnosing biomarkers of ischemic stroke. One of these is lipoprotein-associated phospholipase A2 (Lp-PLA2 ), an enzyme that can hydrolyze circulating oxidized phospholipids, generating proinflammatory lysophosphatidylcholine and promoting the development of atherosclerosis. In the last two decades, a number of studies have revealed that both the concentration and the activity of Lp-PLA2 are independent biomarkers of ischemic stroke. The US Food and Drug Administration (FDA) has approved two tests to determine Lp-PLA2 mass and activity for predicting stroke. In this review, we summarize the biological properties of Lp-PLA2, the detection sensitivity and limitations of Lp-PLA2 measurement, the clinical significance and association of Lp-PLA2 in ischemic stroke, and the prospects of therapeutic inhibition of Lp-PLA2 as an intervention and treatment.